Inside cyber warfare - Carr, Jeffrey (Beijing ; Sebastopol, CA : O'Reilly, 2012)
When the Stuxnet computer worm damaged the Iranian nuclear program in 2010, the public got a glimpse into modern cyber warfare without truly realizing the scope of this global conflict. Inside Cyber Warfare provides details on how nations, groups, and individuals throughout the world increasingly rely on Internet attacks to gain military, political, and economic advantages over their adversaries. This updated second edition takes a detailed look at the complex domain of cyberspace, and the players and strategies involved. You'll discover how sophisticated hackers working on behalf of states or organized crime patiently play a high-stakes game that could target anyone, regardless of affiliation or nationality. Discover how Russian investment in social networks benefits the Kremlin. Learn the role of social networks in fomenting revolution in the Middle East and Northern Africa. Explore the rise of anarchist groups such as Anonymous and LulzSec. Look inside cyber warfare capabilities of nations including China and Israel. Understand how the U.S. can legally engage in covert cyber operations. Learn how the Intellectual Property war has become the primary focus of state-sponsored cyber operations.
Assessing the problem -- The rise of the nonstate hacker -- The legal status of cyber warfare -- Responding to international cyber attacks as acts of war -- The intelligence component to cyber warfare -- Nonstate hackers and the social web -- Follow the money -- Organized crime in cyberspace -- Investigating attribution -- Weaponizing malware -- The role of cyber in military doctrine -- A cyber early warning model -- Advice for policymakers from the field -- Conducting operations in the cyber-space-time continuum -- The Russian Federation: Information warfare framework -- Cyber warfare capabilities by nation-state -- U.S. Department of Defense Cyber Command and organizational structure -- Active defense for cyber: A legal framework for covert countermeasures.
"Mapping the cyber underworld"--Cover.
Includes bibliographical references and index.
Keywords: Computer crimes; Cyberterrorism; Information warfare; Terrorism; Computer crimes; Cyberterrorism; Information warfare; Computer crimes